The prognostic value of 18F-PSMA-1007 PET/CT in predicting pathological upgrading of newly diagnosed prostate cancer from systematic biopsy to radical prostatectomy - Zheng, Anqi; Wang, Zhuonan; Luo, Liang; Chang, Ruxi; Gao, Jungang; Wang, Bo; Duan, Xiaoyi (Frontiers in Oncology, 2023)
Objective This study aimed to evaluate predictors for upgrading of newly diagnosed prostate cancer from systematic biopsy (SB) to radical prostatectomy (RP) using fluorine-18 prostate-specific membrane antigen 1007 (18F-PSMA-1007) positron emission tomography/computed tomography (PET/CT) and association with clinical parameters. Materials and methods We retrospectively collected data from biopsy-confirmed prostate cancer (PCa) patients who underwent 18F-PSMA-1007 PET/CT prior to RP from July 2019 and October 2022. Imaging characteristics derived from 18F-PSMA-1007 PET/CT and clinical parameters were compared in patients of pathological upgrading and concordance subgroups. Univariable and multivariable logistic regressions were performed to analyze factors predicting histopathological upgrading from SB to RP specimens. Discrimination ability of independent predictors was further evaluated by receiver operating characteristic (ROC) analysis with corresponding area under the curve (AUC). Results Pathological upgrading occurred in 26.97% (41/152) PCa patients, and 23.03% (35/152) of all patients experienced pathological downgrading. Concordance rate reached 50% (76/152). International Society of Urological Pathology grade group (ISUP GG) 1(77.78%) and ISUP GG 2 (65.22%) biopsies were related with the highest rate of upgrading. Multivariable logistic regression analyses showed that prostate volume (OR= 0.933; 95% CI, 0.887–0.982; p = 0.008), ISUP GG 1 vs. 4 (OR= 13.856; 95% CI: 2.467–77.831; p = 0.003), and total uptake of PSMA-avid lesions (PSMA-TL) (OR = 1.003; 95% CI, 1.000–1.006; p = 0.029) were found to be independent risk factors of pathological upgrading after RP. The AUCs and corresponding sensitivity and specificity of the independent predictors of synthesis for upgrading were 0.839, 78.00%, and 83.30% respectively, which showed good discrimination capacity. Conclusion 18F-PSMA-1007 PET/CT may help to predict pathological upgrading between biopsy and RP specimens, particularly for ISUP GG 1 and ISUP GG 2 patients with higher PSMA-TL and smaller prostate volume.